Covalent tethering of functional groups to proteins and substrates therefor - DARZINS ALDIS; ENCELL LANCE; WOOD MONIKA G; ZIMPRICH CHAD; KLAUBERT DIETER; LOS GEORGYI V; WOOD KEITH V; MCDOUGALL MARK (2008)
A mutant hydrolase optionally fused to a protein of interest is provided. The mutant hydrolase is capable of forming a bond with a substrate for the corresponding nonmutant (wild-type) hydrolase which is more stable than the bond formed between the wild-type hydrolase and the substrate and has at least two amino acid substitutions relative to the wild-type hydrolase. Substrates for hydrolases comprising one or more functional groups are also provided, as well as methods of using the mutant hydrolase and the substrates of the invention. Also provided is a fusion protein capable of forming a stable bond with a substrate and cells which express the fusion protein.